Bridging the Digital Gap: A Systematic Review on UI/UX Design Considerations for Elderly-friendly Digital Wallets - Nur Alfreeana, Alfie; Jonathan, Sidi; Syahrul Nizam, Junaini; Wang, Yin Chai; Edwin, Mit; Remmy, Gedat (2023)
In an era defined by rapid technological innovation, inclusivity in digital design emerges as a critical yet often overlooked aspect. However, seniors and older citizens often grapple with complex interfaces and sophisticated technology, leading to their digital marginalization. This paper offers a detailed systematic literature review of research trends spanning 2018 - 2023. Sourcing from the renowned SCOPUS database, this review identified a limited 13 journal articles conforming to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. These scholarly publications were thoroughly examined and divided into five core themes encapsulating the focal points of this research: gerontechnology, user experience, user interface design, usability testing, and the advantages mobile apps can offer to the elderly. Further, this synthesized review, aiming to enhance the UI/UX design of digital wallets for seniors, could offer substantial insights to researchers and educators while highlighting potential directions for ensuing research.